Modeling of Millimeter-Wave Modulation Characteristics of Semiconductor Lasers under Strong Optical Feedback - Ahmed Bakry (The Scientific World Journal)
This paper presents modeling and simulation on the characteristics of semiconductor laser modulated within a strong optical feedback (OFB-)induced photon-photon resonance over a passband of millimeter (mm) frequencies. Continuous wave (CW) operation of the laser under strong OFB is required to achieve the photon-photon resonance in the mm-wave band. The simulated time-domain characteristics of modulation include the waveforms of the intensity and frequency chirp as well as the associated distortions of the modulated mm-wave signal. The frequency domain characteristics include the intensity modulation (IM) and frequency modulation (FM) responses in addition to the associated relative intensity noise (RIN). The signal characteristics under modulations with both single and two mm-frequencies are considered. The harmonic distortion and the third order intermodulation distortion (IMD3) are examined and the spurious free dynamic range (SFDR) is calculated.